2020
DOI: 10.3389/fonc.2020.00743
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prediction of Lymph Node Metastasis in Patients With Early-T-Stage Non-small Cell Lung Cancer by Machine Learning Algorithms

Abstract: Background: Lymph node metastasis (LNM) is difficult to precisely predict before surgery in patients with early-T-stage non-small cell lung cancer (NSCLC). This study aimed to develop machine learning (ML)-based predictive models for LNM. Methods: Clinical characteristics and imaging features were retrospectively collected from 1,102 NSCLC ≤ 2 cm patients. A total of 23 variables were included to develop predictive models for LNM by multiple ML algorithms. The models were evaluated by the receiver operating ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Previously, our ( 20 ) and other studies ( 19 , 21 23 ) have found that several preoperative factors might be associated with the occurrence of LNM in small-size NSCLC, including serum CEA, tumor size and imaging features such as imaging density. Tumor size was identified as an important predictor for LNM.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Previously, our ( 20 ) and other studies ( 19 , 21 23 ) have found that several preoperative factors might be associated with the occurrence of LNM in small-size NSCLC, including serum CEA, tumor size and imaging features such as imaging density. Tumor size was identified as an important predictor for LNM.…”
Section: Discussionmentioning
confidence: 71%
“…Thirdly, our study did not involve all clinicopathological characteristics. In our previous (20) and other studies (31), maximal standardized uptake value (SUV max ), was proved to be an impressive predictive factors for LNM, but was not included. That is because PET scan was not routinely performed for small-size NSCLC, and the variable with many missing values was not suitable for linear regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our study, we tried to enroll clinical, radiographical, and histological characteristics, but no significant difference was observed among these three groups for all variables ( Table 3). However, in our previous study, many characteristics demonstrated significantly difference between node-positive and node-negative patients (30). Thus, this study indicated that patients with positive nodes, whether N1, SN2, or N2, shared certain consistency of manifested characteristics.…”
Section: Discussionmentioning
confidence: 50%
“…Even with active anti-tumor treatment, some patients have progressive disease and distant metastasis and require further treatment. TNM stage is an important prognostic biomarker of lung cancer, 17 and for early-stage NSCLC, the 5-year survival rate is more than 70%. 18,19 However, many patients have distant metastasis at the initial diagnosis of early T stages (diameter≤5cm).…”
Section: Discussionmentioning
confidence: 99%